2009
DOI: 10.1007/s00122-009-1052-z
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and association mapping on chromosome 7 using a diverse panel of Chinese germplasm of rice (Oryza sativa L.)

Abstract: The majority of 170 rice accessions used in this study were diverse landraces or varieties from a putative mini-core collection of Chinese germplasm along with some widely used parental lines in genetic analysis or breeding (a few from abroad). The population was genotyped using 84 SSR or InDel markers on chromosome 7 and 48 markers on other chromosomes. The phenotyping of heading date, plant height and panicle length were carried out in different locations for 2 years. Based on morphological characterization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 41 publications
3
37
0
2
Order By: Relevance
“…In this study, a total of 689 alleles were detected with 160 SSR markers, which were randomly distributed across the genome of a panel of 276 accessions, with the average number of alleles per locus being 4.31, ranging from 2 (RM13538) to 8 (RM10920). This is consistent with the 3.9 alleles per locus previously identified in 416 rice accessions, most of which were collected in China, with 100 SSR markers (Jin et al, 2010), and 5 alleles per locus, which were detected in 170 rice accessions from a putative mini-core collection of Chinese germplasms with 132 SSR and InDel markers (Wen et al, 2009). However, the value obtained in the present study was lower than the 7.7 alleles per locus detected in 247 rice accessions from a mini-core collection of Japanese rice landraces using 32 SSR markers, the 11.9 alleles per locus detected in 236 rice accessions from 23 countries with 60 SSR markers, and the 13.47 alleles per locus identified by 70 SSR markers in 217 rice accessions selected from the United States Department of Agriculture (USDA) Rice Genebank (Agrama et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, a total of 689 alleles were detected with 160 SSR markers, which were randomly distributed across the genome of a panel of 276 accessions, with the average number of alleles per locus being 4.31, ranging from 2 (RM13538) to 8 (RM10920). This is consistent with the 3.9 alleles per locus previously identified in 416 rice accessions, most of which were collected in China, with 100 SSR markers (Jin et al, 2010), and 5 alleles per locus, which were detected in 170 rice accessions from a putative mini-core collection of Chinese germplasms with 132 SSR and InDel markers (Wen et al, 2009). However, the value obtained in the present study was lower than the 7.7 alleles per locus detected in 247 rice accessions from a mini-core collection of Japanese rice landraces using 32 SSR markers, the 11.9 alleles per locus detected in 236 rice accessions from 23 countries with 60 SSR markers, and the 13.47 alleles per locus identified by 70 SSR markers in 217 rice accessions selected from the United States Department of Agriculture (USDA) Rice Genebank (Agrama et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…Since association mapping utilizes diverse germplasm, QTLs for many traits can be detected at highresolution in a single study (Neumann et al, 2011;Yu et al, 2009;Breseghello and Sorrells, 2006). Numerous molecular markers have been identified to be associated with different important traits in a wide variety of crops (Wen et al, 2009;Harjes et al, 2008). However, only a few QTL studies have been reported for photosynthetic traits (Wang et al, 2012), probably due to the difficulty in measuring gas exchange parameters under field conditions and the influence of environment on these parameters (Mir et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Association mapping has been first successfully used for genetic studies on some complex human diseases, and it has also been used successfully in various plant species to identify markers associated with a variety of phenotypes in recent years. Significant associations have been identified between SNPs (single nucleotide polymorphisms), RFLP (restriction fragment length polymorphism), AFLP (amplified fragment length polymorphism), SSR (single sequence repeat) markers and varied agronomical or morphological traits in maize Beló et al 2008;Harjes et al 2008), rice (Agrama et al, 2007;Wen et al 2009), barley (Kraakman et al 2006) and soybean (Jun et al 2007). In hexaploid wheat, Breseghello and Sorrels (2006) firstly conducted association test between kernel traits and SSR markers in 95 elite wheat germplasms.…”
Section: Introductionmentioning
confidence: 99%